New Polymeric Composites Derived from Waste PET: Synthesis, Characterization, and Antimicrobial Activity - Kafa Khalaf Hammud; Sahar Hasan Joori; Safauldeen Adnan (Iraqi Journal of Industrial Research)
Many chemical, physical, and biological methods have been applied for plastic pollution as a global environmental problem. Polyethylene terephthalate (PET) is a commonly used polymer for many human life-related applications (food and water containers). In this paper, PET was hydrolyzed in a alcoholic NaOH medium at 110°C to obtain sodium terephthalate (Na-Terephthalate) that refluxed with glycerine and polyvinyl alcohol (PVA). PVA-terephthalate polymeric composite formed a flexible thin film. Other composites were prepared using PVA, Na-Terephthalate, and glycerine and NiCl2.6H2O, ZnSO4.7H2O, Sr(NO3)2, or FeCl3. All PVA-terephthalate composites were characterized using FTIR, XRD, SEM, and DTA. Additionally, all prepared composites were screened for their microbial activity against E. coli, S. aureus, P. aeruginosa, and Candida albicans. The PVA-terephthalate composite showed a good to moderate inhibition zone towards S. aureus, P. aeruginosa, and Candida albicans. All metallic composites showed a negative response against P. aeruginosa and Candida albicans. The Zinc composite exhibited a noticeable inhibition zone against E. coli and S. aureus. These newly prepared composites (PVA-terephthalate, Nickel, and Iron composites) were evaluated for endo- and/or exothermic DTA peaks. The exothermic temperature of the Nickel composite was higher than the Iron composite, while PVA-terephthalate did not show any exothermic reaction. The obtained characteristics suggest promising materials for industrial applications such as seedling planting bags, food coating, and packaging materials, starting with minimizing PET quantity in the environment. The addition of metal salt to the blend composition may be a good suggestion in other research fields such as optical or electric applications.